Investment Opportunity Set sebagai Pemoderasi Pengaruh Profitabilitas, Kepemilikan Manajerial, dan Ukuran Perusahaan terhadap Kebijakan Utang - Suriani Ginting; Seti Eli Larosa; Sonya Enda Natasha S Pandia (Universitas Medan Area, 2021)
This research aims to determine and analyze the influence of Profitability, Managerial Ownership, Firm Size in Debt Policy with Investment Opportunity Set as a moderating variable. The populations in this research were 177 companies. The sampling method in this research was purposive sampling and obtained 19 sample companies. Analysis of data method used multiple linear regression analysis and regression analysis moderating variable with absolute difference value method.The result of analysis shows that simultaneously Profitability, Managerial Ownership, Firm Size have a significant effect on Debt Policy. Partially, Profitability, Managerial Ownerdhip have a significant effect on Debt Policy. While Firm Size have a not significant on Debt Policy. And Investment Opportunity Set is not able to moderate the relationship between Profitability, Managerial Ownership, and Firm Size